Exploring the Role of Frenkel Exercises in Enhancing Dynamic Balance and Motor Function in the Aged With Neurological Disorders: A Systematic Review - Alireza Vasiee; Faraz Tayyar-Iravanlou; Fatemeh Rahmani; Azin Zeidani; MohammadHossein Sahami Gilan (Journal of Aging Research)
Conclusion: Frenkel exercises improve dynamic balance and motor function while lowering fall risk in elderly individuals with neurological disorders. Its simplicity and low cost make it a practical option, but more long-term studies are needed to confirm these benefits.